2018
DOI: 10.1007/s11420-017-9600-6
|View full text |Cite
|
Sign up to set email alerts
|

Online Patient Ratings Are Not Correlated with Total Knee Replacement Surgeon–Specific Outcomes

Abstract: There was no correlation between surgeon-specific TKR outcome measures and online patient ratings. We therefore advise that patients exert caution when interpreting ratings on these websites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Table 2 also includes the summaries of the relationship between PORs and clinical outcomes and other quality measures. Most of the 9 studies on the relationships of PORs and clinical outcomes reported weak or no relationship [11,31,33,52,53,56,66,68,69]. For instance, a study of PORs on cardiologists found no correlation (Spearman ρ=−0.06; P =.13) between PORs and mortality rates following the coronary artery bypass surgery [56].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 also includes the summaries of the relationship between PORs and clinical outcomes and other quality measures. Most of the 9 studies on the relationships of PORs and clinical outcomes reported weak or no relationship [11,31,33,52,53,56,66,68,69]. For instance, a study of PORs on cardiologists found no correlation (Spearman ρ=−0.06; P =.13) between PORs and mortality rates following the coronary artery bypass surgery [56].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies argue that patients are not well-suited to evaluate physician quality because of the information asymmetry between patients and care providers [ 69 ]. In addition, several studies emphasize that ratings and reviews of patients are not correlated to clinical measures of physician quality [ 70 , 71 ]. Despite these shortcomings, PRWs have surged in popularity and have become instrumental in shaping prospective patients’ opinions.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these investigated outcomes include infection rate, re-admission rate, revisional surgery rate, and risk-adjusted mortality rate, in surgeries such as total knee replacements, hernia repairs, and coronary artery bypass grafting. All of these studies failed to find any correlation between a surgeon's online ratings and their measurable outcomes, including those listed above [16][17][18]. These results seriously undermine the utility of such websites, however are unlikely to be realized by the average health care consumer.…”
Section: Online Era: Social Media and Patient Influencementioning
confidence: 99%